A Study of Technology Acceptance Model Affecting on Attitude toward the Use of Android Smartphone - Hansanti, Songporn (Business Administration and Management Journal Review, 2023)
This aims of this research is to explore 1) The impact of different individual factors on attitudes towards the use of android smart phones, 2) The effect of different perceived of technologies on attitudes towards the use of android smart phones. This research is quantitative research where questionnaires were utilized as a tool to collecting data. The population of the survey were those who have used or using Android smart phones and resided in Bangkok and vicinity provinces. Sample of the research were 385 people. Statistics of this research were one-way Anova Results of the research demonstrated that the samples who were Android smart phone users had high levels of perceived usefulness of technologies, while the ease of use of Android smart phones were at medium level. In terms of personal factors, including the diffential of age, education, occupation and average monthly income were contributed to the attitudes towards the use of Android smart phones, excepting the diffential of genders had no effect on the attitudes toward the use of Android smart phone. Research hypotheses founded that the different perceived of technologies were contributed to the different attitudes towards the use of Android smart phones.